On the incentives to form strategic coalitions in ATM markets - Tobias Wenzel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2008)
This paper studies ATM coalitions in retail banking. We ask when it is profitable for banks to make agreements which ban direct ATM transaction fees. In the case of a coalition banks loose income from ATM transactions but relax competition in the banking market. We find that such agreements are profitable when the interchange fee is sufficiently high. When banks can collude on the interchange they always form a coalition. Coalitions may harm consumers but lead to higher total welfare. Moreover, we find that smaller banks have larger incentives to form ATM coalitions. Investment in ATM networks is typically higher with a coalition.
Keywords: L1; G2; 330; Banking competition; ATM networks; collusion; Bankautomation; Business Network; Wettbewerbsbeschränkung; Bank; Koalition; Theorie